2017
DOI: 10.1002/fuce.201700154
|View full text |Cite
|
Sign up to set email alerts
|

Internal Partial Oxidation Reforming of Butane and Steam Reforming of Ethanol for Anode‐supported Microtubular Solid Oxide Fuel Cells

Abstract: Internal partial oxidation reforming of butane and steam reforming of ethanol were investigated using microtubular solid oxide fuel cells (SOFCs) supported on nickel‐gadolinia doped ceria (Ni‐GDC) anodes for portable power sources in emergency situations and for mobilities, such as vehicles, robots and drones. At an oxygen/carbon (O/C) ratio of 1.0, which is a coking condition in the equilibrium, the Ni‐GDC anode deteriorated for 28 h by internal partial oxidation of butane at 650 °C. However, power generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…To improve internal reforming of ethanol fuel in conventional SOFCs, the primary approach has been to augment or replace the Ni anode electrocatalyst. The most notable catalyst compositions can be classified into four categories: (1) Ni-based anodes such as Ni-YSZ [20,40,41], Ni-GDC [42,43], Ni-CeO2 [44,45], Ni-CZO [46], Ni-BZCYYb [47], Ni-BZCY [22,47], Ni-Al2O3 [22], Ni-SrFeLaCoO3 [48], (2) Ni-free anodes including Cu-CGO [1,41,49], Cu-CeO2 [50,51], Cu-CZO [37], Cu-CeO2-ScSZ [35,52], Ir-CGO [44], Ru-CGO [1], Ru-Cu-CZO [1], Cu-Co(Ru)-CZO [53], Pd-LSCM [54], Ru-LSCM [55], (3) Ni-alloys with Sn [56], Fe [36,48], Co [48,57], and (4) Ni-free alloys such as CuZnAl [58], and CuCoRu [53]. The majority of these studies reported low performance with ethanol (peak power <0.3 W cm -2 at 600-800 ºC), due to the use of inherently low-performing cells, incomplete reforming, or both.…”
Section: Introductionmentioning
confidence: 99%
“…To improve internal reforming of ethanol fuel in conventional SOFCs, the primary approach has been to augment or replace the Ni anode electrocatalyst. The most notable catalyst compositions can be classified into four categories: (1) Ni-based anodes such as Ni-YSZ [20,40,41], Ni-GDC [42,43], Ni-CeO2 [44,45], Ni-CZO [46], Ni-BZCYYb [47], Ni-BZCY [22,47], Ni-Al2O3 [22], Ni-SrFeLaCoO3 [48], (2) Ni-free anodes including Cu-CGO [1,41,49], Cu-CeO2 [50,51], Cu-CZO [37], Cu-CeO2-ScSZ [35,52], Ir-CGO [44], Ru-CGO [1], Ru-Cu-CZO [1], Cu-Co(Ru)-CZO [53], Pd-LSCM [54], Ru-LSCM [55], (3) Ni-alloys with Sn [56], Fe [36,48], Co [48,57], and (4) Ni-free alloys such as CuZnAl [58], and CuCoRu [53]. The majority of these studies reported low performance with ethanol (peak power <0.3 W cm -2 at 600-800 ºC), due to the use of inherently low-performing cells, incomplete reforming, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Performance with ethanol is of particular interest for consumer vehicles, as a replacement for gasoline. Ethanol can be reformed readily on Ni catalyst, and addition of water reduces the likelihood of coking (14). MS-SOFCs with additional Ni infiltrated into the metal support show excellent performance for direct internal reforming of ethanolwater blend, Fig 5 . Detailed studies of performance with ethanol reformate and internal reforming of ethanol are available elsewhere (15), and durability studies are ongoing.…”
Section: Fuel Cell Durabilitymentioning
confidence: 98%
“…C 4 H 10 + 2O 2 → 4CO + 5H 2 ∆H 25°C = 316 kJ mol -1 [1] However, the O/C ratio should be more than 1.5 to prevent carbon deposition at 650 o C in the thermodynamic equilibrium (11). Figure 5 shows the current density-voltage and power density characteristics with internal partial oxidation reforming of butane at 650 o C for microtubular cells using Ni-GDC anode.…”
Section: Internal Partial Oxidation Reforming Of Butanementioning
confidence: 99%